Modern diagnostics and treatment of combined congenital cardiovascular system and gastrointestinal tract malformations - Т. Ye. Shumna; M. O. Makarova; O. V. Panchenko (Zaporožskij Medicinskij Žurnal)
Purpose – to share the experience of qualified medical care providing to newborn children born with combined abnormal development.